3(x+2)(x-2)=(3x-4)(x+1)

Simple and best practice solution for 3(x+2)(x-2)=(3x-4)(x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+2)(x-2)=(3x-4)(x+1) equation:



3(x+2)(x-2)=(3x-4)(x+1)
We move all terms to the left:
3(x+2)(x-2)-((3x-4)(x+1))=0
We use the square of the difference formula
x^2-((3x-4)(x+1))-4=0
We multiply parentheses ..
x^2-((+3x^2+3x-4x-4))-4=0
We calculate terms in parentheses: -((+3x^2+3x-4x-4)), so:
(+3x^2+3x-4x-4)
We get rid of parentheses
3x^2+3x-4x-4
We add all the numbers together, and all the variables
3x^2-1x-4
Back to the equation:
-(3x^2-1x-4)
We get rid of parentheses
x^2-3x^2+1x+4-4=0
We add all the numbers together, and all the variables
-2x^2+x=0
a = -2; b = 1; c = 0;
Δ = b2-4ac
Δ = 12-4·(-2)·0
Δ = 1
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{1}=1$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(1)-1}{2*-2}=\frac{-2}{-4} =1/2 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(1)+1}{2*-2}=\frac{0}{-4} =0 $

See similar equations:

| (2x-52)=(3x-22) | | 8k÷3=32 | | 4(-4p+2=-120 | | -(f—-28)=-47 | | 2x-52=180° | | 3(w+7)-7w=5 | | 11=3v+2 | | -80=8-8x | | X^2-78x+1009=0 | | 2x-52+80°=180° | | 5d-9=-27 | | 6x+10+40=180 | | 21(x-4)=7 | | 23-4v=7 | | 16+s=36.94 | | -2=x-10/9 | | 175÷25=7*p | | 3=2x+5x | | (4x-12)^(1/2)+3=x | | 8-6n=-82 | | 15x^2+14x-57=0 | | 6h(6h)=3h | | 3m=2m-5+12 | | 2x+29=3x-29 | | 8(y-8)/3=4y | | -6x-6=6-6x | | 2n-8×3+6=4×8+8 | | 2(z+5)=3z=-15 | | 6t^2+t-20=0 | | 4+a/9=-1 | | 7+12x=32x-3 | | 5(2-x)=2x+7-7x+3 |

Equations solver categories